Progress in Polymeric Micelles for Drug Delivery Applications - Sabna Kotta; Hibah Mubarak Aldawsari; Shaimaa M. Badr-Eldin; Anroop B. Nair; Kamal YT (MDPI AG, 2022)
Polymeric micelles (PMs) have made significant progress in drug delivery applications. A robust core-shell structure, kinetic stability and the inherent ability to solubilize hydrophobic drugs are the highlights of PMs. This review presents the recent advances and understandings of PMs with a focus on the latest drug delivery applications. The types, methods of preparation and characterization of PMs are described along with their applications in oral, parenteral, transdermal, intranasal and other drug delivery systems. The applications of PMs for tumor-targeted delivery have been provided special attention. The safety, quality and stability of PMs in relation to drug delivery are also provided. In addition, advanced polymeric systems and special PMs are also reviewed. The in vitro and in vivo stability assessment of PMs and recent understandings in this area are provided. The patented PMs and clinical trials on PMs for drug delivery applications are considered indicators of their tremendous future applications. Overall, PMs can help overcome many unresolved issues in drug delivery.